AAMP98 デ オコワレタ コウクウキ ニ ヨル エアロゾル チュウ イオン セイブン ソクテイ - 山形, 定; ヤマガタ, サダム; 庄司, 和弘; ショウジ, カツヒロ; 村尾, 直人; ムラオ, ナオト; 太田, 幸雄; オオタ, サチオ; Yamagata, Sadamu; Shoji, Katsuhiro; Murao, Naoto; Ohta, Sachio (2002)
P(論文) 北極圏航空機観測1998 (AAMP 98）中， 大気エアロゾルをガルフストリームIIのインレットから機内に導入し，ディフューザーで減速した後，テフロンフィルター上に捕集した．ディフューザー内の0.3µm以上の粒径を持つ粒子数濃度をフィルターサンプリングのラインと並列につないだオプティカルパーティクルカウンタ（OPC）でモニタ ーした. OPCのデータはシリアル通信でパソコンに転送，記録した．フィルターサンプルは実験室に持ち帰り，イオン交換水で抽出後イオンクロマトグラフを用い、陽・陰イオン濃度を測定した．Cl^- , N02^- , NO3^- , SO4^2-, Na^+ , NH4^+, K^+, Mg^2+, Ca^2＋のイオンが検出された．成層圏にはSO4^2- を含んだエアロゾル層が知られているが，本観測では，これに加えCl^-, Ca^2＋が上空でしばしば検出された． During the Arctic Airborne Measurement Program 1998 (AAMP 98), atmospheric aerosols were collected onto PTFE filters from the inlet of Gulfstream II through a diffuser installed in the cabin. During the sampling the number concentrations of aerosol particles with diameters larger than 0.3 µm were continuously monitored with an optical particle counter (OPC) connected to the diffuser in parallel to the filter sampling line. The data from the OPC were transferred by serial communication to a computer and recorded. The filter samples were brought back to the laboratory, then extracted with ion exchanged water and the concentrations of anions and cations were analyzed by ion chromatography. Detected ions were as follows: Cl^-, N02^-, 1 , N03^-, SO4^2-, Na^+, NH4+, K^+, Mg^2+, Ca^2+. Even at high altitudes Cl^- and Ca^2+ were frequently detected, in addition to SO4^2- , which is known as a major ionic component in the stratosphere. departmental bulletin paper